Pengaruh Tax Planning Terhadap Nilai Perusahaan Pada Perusahaan Property & Real Estate Periode 2016-2020 - Hadrian Ersa Tuari; Meinarni Asnawi; Pascalina V. S. Sesa (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2022)
This study aims to analyze the effect of Tax Planning on Company Value in property & real estate companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Tax planning in this study is measured by cash effective tax rates and book tax difference as independent variables and firm value is measured by price earning ratio as the dependent variable. The sample in this study was purposive sampling with a total of 60 research data. The analysis technique used in this study is quantitative data analysis using the SPSS 16 statistical application. Based on the results of the analysis it is found that cash effective tax rates and book tax difference have an effect on firm value.